A study of attachment anxiety and rejection sensitivity as predictors of academic performance in undergraduate females studying at University of The Bahamas - Lomax, Candera Tamika; Miller, Mary Lou; Holzmann, Gwetheldene L. (International Journal of Bahamian Studies, 2025)
Rejection is a common human experience; however, people respond differently to its occurrence. Employing attachment theory as a framework to examine the extent and presence of rejection sensitivity, this study utilized undergraduate females (N = 191) studying at the University of The Bahamas to explore the relationship between attachment orientation, rejection sensitivity (RS), and academic performance. Demographic data questions and two assessment instruments were combined into an electronic survey platform. The Experience in Close Relationships-Relationships Structured Questionnaire and the Rejection Sensitivity Questionnaire-Personal were used to measure attachment orientation (across five relationship domains) and RS, respectively. The study utilized a hierarchical multiple regression analysis to test the hypotheses. Findings revealed no significant relationship between RS and academic performance. Mom and dad attachment anxiety in Model 3, were significantly related to academic performance. However, there was no significant relationship between RS and academic performance, as indicated in Model 4. The study findings are significant as they respond to the growing need for research that examines factors that influence academic outcomes of Bahamian students at various educational levels. Recommendations for student advisement, counseling, mentorship practices, and future research are presented.